Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Nasi Basi untuk Meningkatkan Produktivitas Hortikultura di Kelurahan Cicenang - Fikri Kusaeri; Evi Roviati (PT. Adriani Mandiri Publisher, 2026)
Organic fertilizers have long been known to farmers before the implementation of the green revolution. After the green revolution, most farmers prefer to use artificial fertilizers because they are practical in use, far less than organic fertilizers, the price is relatively cheap, and easy to obtain. Most farmers are already very dependent on artificial fertilizers, so it can have a negative impact on the development of agricultural production. Growing awareness of farmers will have a negative impact on the use of artificial fertilizers and other modern means on the environment has made agriculture switch from conventional farming. To obtain data in research, researchers must know the techniques and methods of data collection used. The technique used must be in accordance with what will be studied. This study uses qualitative data collection and several data collection methods, namely the document method used to complete the research, in the form of written sources, images and videos. The document will provide information for the research process. Study literature or library research method, this is done by reviewing the literature either from journals, articles, or books related to the research topic.The method used is mentoring farmer groups and being an instructor whose role is to provide direction in the process of making liquid organic fertilizer . This research was conducted on Friday, July 16, 2021. The purpose of this research is to train farmer groups in Cicenang Village in making MOL (Local Mikro Organisms) derived from stale rice waste as liquid organic fertilizer for ho ticultural crops. Based on the results of research through practicum, it was found that the formation of local micro-organisms (MOL) was successful, characterized by the aroma produced resembling the aroma of tapai